2010
DOI: 10.1074/jbc.m109.051862
|View full text |Cite
|
Sign up to set email alerts
|

REH2 RNA Helicase in Kinetoplastid Mitochondria

Abstract: Regulation of gene expression in kinetoplastid mitochondria is largely post-transcriptional and involves the orchestration of polycistronic RNA processing, 3-terminal maturation, RNA editing, turnover, and translation; however, these processes remain poorly studied. Core editing complexes and their U-insertion/deletion activities are relatively well characterized, and a battery of ancillary factors has recently emerged. This study characterized a novel DExH-box RNA helicase, termed here REH2 (RNA editing assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
85
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(88 citation statements)
references
References 55 publications
3
85
0
Order By: Relevance
“…These findings are consistent with the recent report that GAP1/2 associates with the REH2 helicase apart from the MRB1 core (53), as well as with our previous data suggesting a similar association of GAP1/2 with the mitochondrial zinc finger protein, MRB6070 (20). Given the interaction of REH2 with the RNA editing machinery and its impact on RNA editing, it is easy to envision a role for GAP1/2-bound gRNAs in association with REH2 (31,52,53). In contrast, our results indicate that TbRGG3 is not involved in RNA editing, and thus its function likely does not involve gRNAs.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…These findings are consistent with the recent report that GAP1/2 associates with the REH2 helicase apart from the MRB1 core (53), as well as with our previous data suggesting a similar association of GAP1/2 with the mitochondrial zinc finger protein, MRB6070 (20). Given the interaction of REH2 with the RNA editing machinery and its impact on RNA editing, it is easy to envision a role for GAP1/2-bound gRNAs in association with REH2 (31,52,53). In contrast, our results indicate that TbRGG3 is not involved in RNA editing, and thus its function likely does not involve gRNAs.…”
Section: Discussionsupporting
confidence: 81%
“…We hypothesized that the T. brucei TbRGG3 protein plays a role in mitochondrial RNA biology due to its reported association with the RNA binding proteins, GAP1/2, TbRGG1, and REH2, as well as the large ribosomal subunit (13,25,31). The arginine-glycinerich nature of TbRGG3 further suggested that it possesses intrinsic RNA binding ability (21,32,33).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations